Investigate Effects of Microstructures on Nanoconfined Water Flow Behaviors from Viscous Dissipation Perspectives - Han Wang; Yuliang Su; Rui Qiao; Jiandong Wang; Wendong Wang (Transport in Porous Media, 2021)

Increasing nitrogen supply to phosphorus-deficient Medicago sativa decreases shoot growth and enhances root exudation of tartrate to discharge surplus carbon dependent on nitrogen form - Honghua He; Zekun Zhang; Qi Peng; Chao Chang; Rui Su; Xiao Cheng; Yingxin Li; Jiayin Pang; Sheng Du; Hans Lambers (Plant and Soil, 2021)

Summery Intra-Tidal Variations of Suspended Sediment Transportation – Topographical Response and Dynamical Mechanism in the Aoshan Bay and Surrounding Area, Shandong Peninsula - Yan Wang; Yanguang Dou; Liang Zou; Fei Gao; Dapeng Su; Rui Hu; Baojing Yue; Biying Xue (Journal of Ocean University of China, 2021)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Rhizosphere-associated nosZII microbial community of Phragmites australis and its influence on nitrous oxide emissions in two different regions - Rui Su; Rui Huang; Jin Zeng; Dayong Zhao; Rujia He; Zhongbo Yu; Qinglong L. Wu (Journal of Soils and Sediments, 2021)

A novel amorphous solid dispersion based on drug–polymer complexation - Fan Meng; Rui Ferreira; Yongchao Su; Feng Zhang (Drug Delivery and Translational Research, 2021)

The Identification and Prediction in Abundance Variation of Atlantic Cod via Long Short-Term Memory With Periodicity, Time–Frequency Co-movement, and Lead-Lag Effect Across Sea Surface Temperature, Sea Surface Salinity, Catches, and Prey Biomass From 1919 to 2016 - Rui Nian; Qiang Yuan; Hui He; Xue Geng; Chi-Wei Su; Bo He; Amaury Lendasse (Frontiers in Marine Science, 2021)
The population of Atlantic cod significantly contributes to the prosperity of fishery production in the world. In this paper, we quantitatively investigate the global abundance variation in Atlantic cod from 1919 to 2016, in favor of spatiotemporal interactions over manifold impact factors at local observation sites, and propose to explore the predictive mechanism with the help of its periodicity, time–frequency co-movement, and lead-lag effects, via long short-term memory (LSTM). We first integrate evidences yielded from wavelet coefficients, to suggest that the abundance variation potentially follows a 36-year major cycle and 24-year secondary cycle at the time scales of 55 years and 37 years. We further evaluate the responses of Atlantic cod abundance to the external impact factors, including sea surface temperature (SST), catches, prey biomass, and sea surface salinity (SSS), in aid of the wavelet coherence and phase difference, which allows us to identify the dominantly correlative factors and capture the leading roles along the time domain and then divide the responses around the recent 60 years into three stages: before 1985, 1985–1995, and after 1995. At the first stage, the reason for the decline in abundance could be mainly attributed to the rapid rise of fish catches. At the second stage, the impact of SST and SSS also provides significant indices, besides overfishing; meanwhile, the mortality of primary producers and forced migration of fish species indirectly cause the decline. At the third stage, warming SST and growing SSS directly led to the decrease of abundance. Finally, we establish one ensemble of LSTM-SAE architecture to comprehensively reflect the predictive patterns at each stage. It has been demonstrated from experimental results that the models behaved better when intentionally feeding with the dominantly correlative multivariate inputs, instead of either all factors or only the abundance. The proposed scheme provides opportunities to symmetrically identify the underlying predictive attributes of Atlantic cod abundance and potentially perform as the quantitative references in reasonably making fishing decision. With the rapid development in deep learning capabilities, it is hopeful to expect better predictions of the responses to global changes, not only for Atlantic cod but also for other fish species and the ecosystem as a whole.

An IPSO-RNN machine learning model for soil landslide displacement prediction - Tao Zheng; Qi hua Zhao; Jian bo Hu; Jun feng Jiang; Rui Su (Arabian Journal of Geosciences, 2021)

Contrasting pathways of carbon sequestration in paddy and upland soils - Xiangbi Chen; Yajun Hu; Yinhang Xia; Shengmeng Zheng; Chong Ma; Yichao Rui; Hongbo He; Daoyou Huang; Zhenhua Zhang; Tida Ge; Jinshui Wu; Georg Guggenberger; et al. (Global Change Biology, 2021)
Paddy soils make up the largest anthropogenic wetlands on earth, and are characterized by a prominent potential for organic carbon (C) sequestration. By quantifying the plant‐ and microbial‐derived C in soils across four climate zones, we identified that organic C accrual is achieved via contrasting pathways in paddy and upland soils. Paddies are 39%–127% more efficient in soil organic C (SOC) sequestration than their adjacent upland counterparts, with greater differences in warmer than cooler climates. Upland soils are more replenished by microbial‐derived C, whereas paddy soils are enriched with a greater proportion of plant‐derived C, because of the retarded microbial decomposition under anaerobic conditions induced by the flooding of paddies. Under both land‐use types, the maximal contribution of plant residues to SOC is at intermediate mean annual temperature (15–20°C), neutral soil (pH~7.3), and low clay/sand ratio. By contrast, high temperature (~24°C), low soil pH (~5), and large clay/sand ratio are favorable for strengthening the contribution of microbial necromass. The greater contribution of microbial necromass to SOC in waterlogged paddies in warmer climates is likely due to the fast anabolism from bacteria, whereas fungi are unlikely to be involved as they are aerobic. In the scenario of land‐use conversion from paddy to upland, a total of 504 Tg C may be lost as CO 2 from paddy soils (0–15 cm) solely in eastern China, with 90% released from the less protected plant‐derived C. Hence, preserving paddy systems and other anthropogenic wetlands and increasing their C storage through sustainable management are critical for maintaining global soil C stock and mitigating climate change.

A functional chromogen gene C from wild rice is involved in a different anthocyanin biosynthesis pathway in indica and japonica - Weihua Qiao; Yanyan Wang; Rui Xu; Ziyi Yang; Yan Sun; Long Su; Lizhen Zhang; Junrui Wang; Jingfen Huang; Xiaoming Zheng; Shijia Liu; Yunlu Tian; et al. (Theoretical and Applied Genetics, 2021)

Correction to: Strong phosphorus (P)-zinc (Zn) interactions in a calcareous soil-alfalfa system suggest that rational P fertilization should be considered for Zn biofortification on Zn-deficient soils and phytoremediation of Zn-contaminated soils - Honghua He; Miaomiao Wu; Rui Su; Zekun Zhang; Chao Chang; Qi Peng; Zhigang Dong; Jiayin Pang; Hans Lambers (Plant and Soil, 2021)

Effects of oxytetracycline on plant growth, phosphorus uptake, and carboxylates in the rhizosheath of alfalfa - Zekun Zhang; Rui Su; Chao Chang; Xiao Cheng; Qi Peng; Hans Lambers; Honghua He (Plant and Soil, 2021)

Strong phosphorus (P)-zinc (Zn) interactions in a calcareous soil-alfalfa system suggest that rational P fertilization should be considered for Zn biofortification on Zn-deficient soils and phytoremediation of Zn-contaminated soils - Honghua He; Miaomiao Wu; Rui Su; Zekun Zhang; Chao Chang; Qi Peng; Zhigang Dong; Jiayin Pang; Hans Lambers (Plant and Soil, 2021)

An NGO disaster relief network for small and medium-scale natural hazards in China - Yi Lu; Chengyan Zhan; Rui Li; Min Su (Natural Hazards, 2021)

Experimental validation of a new semi-empirical impact force model of the dry granular flow impact against a rigid barrier - Yuan-Jun Jiang; Xiao-Yi Fan; Li-Jun Su; Si-you Xiao; Jing Sui; Rui-Xiao Zhang; Yue Song; Zhi-Wen Shen (Landslides, 2021)

Rescue effects of Se-enriched rice on physiological and biochemical characteristics in cadmium poisoning mice - Yang Su; Ling Li; Muhammad Umer Farooq; Xin Huang; Tengda Zheng; Yu Jie Zhang; Hla Hla Ei; Faiz Hussain Panhwar; Zhichen Tang; Rui Zeng; Yuanke Liang; Xiaoying Ye; et al. (Environmental Science and Pollution Research, 2021)

BeiDou-3 broadcast clock estimation by integration of observations of regional tracking stations and inter-satellite links - Yufei Yang; Yuanxi Yang; Xiaogong Hu; Chengpan Tang; Rui Guo; Zhanshi Zhou; Junyi Xu; Junyang Pan; Mudan Su (GPS Solutions, 2021)

Protective equipment and health education program could benefit students from dust pollution - Yi-Chen Chiang; Xian Li; Chun-Yang Lee; Jia Rui; Chiung-Wen Hu; Hao-Jan Yang; Szu-Chieh Chen; Tianmu Chen; Yanhua Su; Chung-Yih Kuo; Shao-Chieh Hsueh (Air Quality, Atmosphere & Health, 2021)

The geological characteristics of the large- and medium-sized gas fields in the South China Sea - Gongcheng Zhang; Dongdong Wang; Lei Lan; Shixiang Liu; Long Su; Long Wang; Wu Tang; Jia Guo; Rui Sun (Acta Oceanologica Sinica, 2021)

Aerosolization Performance, Antitussive Effect and Local Toxicity of Naringenin-Hydroxypropyl-β-Cyclodextrin Inhalation Solution for Pulmonary Delivery - Minyi Guan; Xuan Zeng; Rui Shi; Yuying Zheng; Weiyang Fan; Weiwei Su (AAPS PharmSciTech, 2021)